Enzyme-catalyzed peptide cyclization. (December 2017) - Schmidt, Marcel; Toplak, Ana; Quaedflieg, Peter J.L.M.; van Maarseveen, Jan H.; Nuijens, Timo
Graphical abstract: Abstract : The recent advancement of peptide macrocycles as promising therapeutics creates a need for novel methodologies for their efficient synthesis and (large scale) production. Within this context, due to the favorable properties of biocatalysts, enzyme-mediated methodologies have gained great interest. Enzymes such as sortase A, butelase 1, peptiligase and omniligase-1 represent extremely powerful and valuable enzymatic tools for peptide ligation, since they can be applied to generate complex cyclic peptides with exquisite biological activity. Therefore, the use of enzymatic strategies will effectively supplement the scope of existing chemical methodologies and will accelerate the development of future cyclic peptide therapeutics. The advantages and disadvantages of the different enzymatic methodologies will be discussed in this review.